Предмет: Алгебра,
автор: nikishev0102
преобразуйте выражение в многочлен стандартного вида
а) 2х квадрат (х-3у)
б)(2х-3у) (3у+2х)
в) (а+б) (а-б) (а+б)
Ответы
Автор ответа:
2
2x^3-6xy
9y^2-4x^2=-4x^2+9y^2
(а^2-б^2)(а+б)=а^3-аб^2+а^2б-б^3
9y^2-4x^2=-4x^2+9y^2
(а^2-б^2)(а+б)=а^3-аб^2+а^2б-б^3
Похожие вопросы
Предмет: Алгебра,
автор: pashaevimran43
Предмет: Русский язык,
автор: kirillkaraani
Предмет: Математика,
автор: marselkarimov886
Предмет: География,
автор: sdfggcvhj
Предмет: Математика,
автор: b22222222222222